Storytelling´s history in advertising: a professional approach from creative strategies - Vizcaíno-Alcantud, Pablo (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
The concept of storytelling lacks a theoretical corpus that points to the origin of its use in advertising. Therefore, the aim of this research is to know the historical affiliations of the application of storytelling in advertising, finding its most relevant milestones from the creative strategies. The main conclusion is that advertising, as a profession, is aware of the importance of storytelling, thanks to David Ogilvy. It also indicates that advertising, even before being considered a discipline, has had a narrative component inoculated in a natural way, regardless of the medium and the creative strategies used.